Efficiency analysis of major microfinance institutions in Bangladesh: a Malmquist index approach - Azad, M.A.K.; Masum, A.K.M.; Munisamy, S.; Sharmin, D.F. (Springer Verlag, 2016)
Microfinance institutions (MFIs) have dual objectives- reaching under privileged households for poverty easing and achieving financial sustainability. This paper investigates the efficiency of major 15 MFIs in Bangladesh using Malmquist index (MI) over the period 2008–2012. A balanced panel dataset of 75 observations is used. The results from MI are decomposed into three efficiency scores—technical efficiency (TCH), scale efficiency (SE) and pure efficiency (PE). The empirical findings indicate that MFIs are experienced an excellent annual efficiency progress (93.5 %) which was mainly because of PE. PE measures the capacity of optimizing minimum input to produce maximum output by reducing production wastage. This outstanding growth was an outcome of country’s ever best economic settings before 2008. However, from 2009 onward, a substantial efficiency regresses is observed. The results also signify that the major MFIs have less capacity to work at their optimal scales. The contribution of SE is very low (only 2.2 %) compared to total efficiency progress. Findings from TCH indicate that the overall frontier is moving relatively slow in an outward direction (only 3.7 % of TCH progress).